2021
DOI: 10.1111/2041-210x.13716
|View full text |Cite
|
Sign up to set email alerts
|

Dealing with software complexity in individual‐based models

Abstract: After a slow start in the 1980s, individual-based models (IBMs, also known as agent-based models or mechanistic simulation models) have found growing acceptance as a tool of ecological research (DeAngelis & Grimm, 2014;Grimm & Railsback, 2005).Over the past decade, they have been continuously expanded to simulate increasingly complex macroecological (e.g. Cabral &

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 70 publications
0
16
0
Order By: Relevance
“…GeMM is implemented in Julia with the Distributions.jl package (Bezanson et al, 2017 ; Lin et al, 2021 ), while data preparation and analysis for this study was carried out in R 4.0.4 with the tidyverse packages (R Core Team, 2021 ; Wickham et al, 2019 ). Software development and verification followed best practice as described in Vedder, Ankenbrand, and Cabral ( 2021 ). The full model description following the ODD protocol (Grimm et al, 2010 ) can be found in the Supplementary Materials .…”
Section: Methodsmentioning
confidence: 99%
“…GeMM is implemented in Julia with the Distributions.jl package (Bezanson et al, 2017 ; Lin et al, 2021 ), while data preparation and analysis for this study was carried out in R 4.0.4 with the tidyverse packages (R Core Team, 2021 ; Wickham et al, 2019 ). Software development and verification followed best practice as described in Vedder, Ankenbrand, and Cabral ( 2021 ). The full model description following the ODD protocol (Grimm et al, 2010 ) can be found in the Supplementary Materials .…”
Section: Methodsmentioning
confidence: 99%
“…Developing software is a highly complex activity and the means that are used to build the final product are extremely volatile. Poorly formulated and dynamic user requirements, the high number of people involved in the process, and the interaction of the program being developed with others in the same system contribute to this complexity [19,20]. San Cristóbal et al [21] add that complex problems are usually difficult to predict or are even unpredictable.…”
Section: From Small-scale To Large-scale Agilementioning
confidence: 99%
“…Our kit adds to the efforts of Wilson and colleagues in promoting the “best” [ 9 ] or at least “good enough” [ 10 ] practices in scientific computing. Below, we briefly comment other practices that should be implemented alongside this kit.…”
Section: Introductionmentioning
confidence: 99%
“…We focus on the use of code for modeling, data processing, and presentation. For ecological software, there is a variety of guidelines for publication (e.g., [8][9][10][11]). Moreover, the very work of software development forces authors to apply good practices established in Computer Science to facilitate understanding, such as code documentation and functional programming (i.e., writing your own functions, [9]).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation